2021
DOI: 10.1007/s11701-021-01302-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of simulation training and new 3D computer-generated synthetic organs for robotic surgery education

Abstract: We conducted a comprehensive review of surgical simulation models used in robotic surgery education. We present an assessment of the validity and cost-effectiveness of virtual and augmented reality simulation, animal, cadaver and synthetic organ models. Face, content, construct, concurrent and predictive validity criteria were applied to each simulation model. There are six major commercial simulation machines available for robot-assisted surgery. The validity of virtual reality (VR) simulation curricula for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…There must always be the possibility to treat the patient in open surgery and to deal with complications. 15 Azadi et al reported that there are various training curricula, virtual reality simulators and other robotic training tools developed to enhance robotic surgical education and improve surgical skills. 16 Additionally, docking time is a limiting time factor which improves with increasing experience of the surgical team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There must always be the possibility to treat the patient in open surgery and to deal with complications. 15 Azadi et al reported that there are various training curricula, virtual reality simulators and other robotic training tools developed to enhance robotic surgical education and improve surgical skills. 16 Additionally, docking time is a limiting time factor which improves with increasing experience of the surgical team.…”
Section: Discussionmentioning
confidence: 99%
“…It needs a lot of surgical experience and expertise and should not be underestimated. There must always be the possibility to treat the patient in open surgery and to deal with complications 15 . Azadi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of AR, MR, VR, and 3D printing enables efficient training of physicians [ 280 ]. Preoperative evaluation and simulation using 3D imaging data allow surgeons to gain valuable experience and preoperatively practice surgical steps in a safe setting [ 281 ]. Additionally, these technologies allow real surgeries to be supervised by telepresence [ 282 ].…”
Section: Exponential Innovationsmentioning
confidence: 99%
“…These curricula have previously enabled validation of simulation-based training in robotic surgery, with consensus opinion supporting this approach [3][4][5]. Despite the availability of multiple virtual reality simulators for robotic training [6], currently only the DaVinci Skills ® Simulator™ and the dV-Trainer ® have face, content, construct, concurrent and predictive validity [7] and Da Vinci technology currently dominates robotic education and training.…”
Section: Introductionmentioning
confidence: 99%